Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 350,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

This questions seems ackward. I get two scenarios - 9 and 3 and since d has to be +ve D (3) is the answer

If E is the answer then |d -9| = |9 -9| = 0 which is not possible.

What is the source of your question?

This is how I solved : |d-9|=2d

=> d> 0, d-9 =2d ->d = -9 but this contradicts the assumption d>0

=> d<0 , -(d-9 ) = 2d -d+9=2d 3d =9 =>d=3

You're almost there, except you made a small confusion that led to a contradiction by the end of your proof too: you conclude with d=3 when you assumed d<0 to make the calculations

This is because |d-9| = d-9 when d \(\ge\) 9 and 9-d when d \(\le\) 9 (and not 0)

=> d> 0, d-9 =2d ->d = -9 but this contradicts the assumption d>0

=> d<0 , -(d-9 ) = 2d -d+9=2d 3d =9 =>d=3[/quote] You're almost there, except you made a small confusion that led to a contradiction by the end of your proof too: you conclude with d=3 when you assumed d<0 to make the calculations

This is because |d-9| = d-9 when d \(\ge\) 9 and 9-d when d \(\le\) 9 (and not 0)[/quote]